Real-Time Observations of Leaf Vitality Extinction by Dynamic Speckle Imaging - Elise Colin; Enrique Garcia-Caurel; Karine Adeline; Aurélien Plyer; Xavier Orlik (Photonics)
Sap flow within a leaf is a critical indicator of plant vitality and health. This paper introduces an easy-to-use, non-invasive and real-time imaging method for sap microcirculation imaging. From the coherent backscattering of light on a leaf, we show that the acquisition frequency of dynamic speckle can be linked to the microcirculation speed inside the leaf. Unlike conventional methods based on speckle contrast, which use integration times long enough to observe temporal decorrelation within a single image, our approach operates in a regime where speckle patterns appear ‘frozen’ in each frame of a given sequence. This ‘frozen’ state implies that any decorrelation of the speckle pattern within a frame is negligible. However, between successive frames, decorrelation becomes substantial, and it is this inter-frame decorrelation that enables the extraction of dynamic information. In this context, the integration time primarily influences the radiometric levels, while the frame acquisition rate emerges as the key parameter for generating activity index maps. Thus, by accessing different ranges of sap flow activity levels by varying the frame acquisition rate, we reveal, in a non-invasive way, the anatomy of the leaf’s circulatory network with unprecedented richness. We experimentally validate the ability of the method to characterize the vitality of a fig leaf in real time by observing the continuous decrease in sap circulation, first in the smaller vessels and then in the larger ones, following the cutting of the leaf over a 48 h period.